ECOLOGICAL CHANGES IN INDUSTRIALIZED AREAS - Jobborov Bakhrom Turgunovich,; Gadoeva Validaxon Ikrom qizi,; Erkinova Shahinabonu Olmos qizi, (Лучшие интеллектуальные исследования, 2024)
Annotation: The state provides information on soil pollution with toxic substances emitted by thought, agriculture and motor transport. Such methods of technical and biological reclamation of contaminated soils have been studied.